THE EFFECT OF COMPETENCE, COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE AT THE HEAD OFFICE PT. ALNS ANGLO EASTERN INDONESIA - Dedi Bernard (International Journal Management and Economic, 2024)
This study uses a quantitative approach that combines data collection methods through surveys and observations. In this approach, a dual paradigm is applied by involving three independent variables and one dependent variable. The choice of this type of design is because this study will empirically test the relationship between competence, compensation, and motivation on employee performance at PT. Alns Anglo Eastern Indonesia Anglo Eastern Indonesia. Population is employee  PT. Alns Anglo Eastern Indonesia with amount 161 respondents. This research using the questionnaire data that was studied, data analysis using device soft SPSS Statistics version 21. Data testing with descriptive statistical tests, classical tests and hypothesis tests From the results of this study indicate that simultaneously, competence, compensation and motivation have a positive effect on employee performance achievement at PT. ALNS Anglo Eastern Indonesia. Partially, competence and motivation have an effect on employee performance, while compensation does not have an effect on employee performance.